360° Video virtual reality exposure therapy for public speaking anxiety: A randomized controlled trial. (October 2021) - Reeves, Rachel; Elliott, Adam; Curran, David; Dyer, Kevin; Hanna, Donncha
Highlights: 360° VRET is an effective stand-alone intervention for public speaking anxiety. 360° VRET for public speaking anxiety generalizes to interrelated conditions. Treatment gains following 360° VRET were maintained at 10 week follow-up. Emotion-evoking virtual reality videos were more efficacious than neutral videos. Abstract: Public speaking anxiety (PSA) is a prevalent condition which is highly interrelated with social anxiety. PSA can be effectively treated with exposure therapy. Virtual reality exposure therapy (VRET) is increasingly being explored as a novel and cost-effective mode of treatment. No previous randomized controlled trial has examined whether stand-alone 360° video VRET is an effective intervention for treating PSA and interrelated disorder relevant fears. Further, studies have not explored whether 360° video content influences VRET outcomes. Participants with high PSA (n = 51) were randomly allocated to: 360° video VRET incorporating stimuli of audiences (360°Audience) (n = 17), 360° video VRET incorporating stimuli of empty rooms (360°Empty) (n = 16) and no treatment control (n = 18). Outcomes were measured over five time-points. Mixed ANOVA revealed a significant interaction between time and intervention group for PSA, social anxiety and fear of negative evaluation (FNE). Within-group analysis demonstrated there was a significant pre-intervention to post-intervention reduction across measures for both 360° video VRET groups: PSA 360°Audience ( η p 2 = .90, p< .001), 360°Empty ( η p 2 = .71, p < .001); social anxiety 360°Audience ( η p 2 = .49, p=. 002), 360°Empty ( η p 2 = .39, p = .009); FNE 360°Audience ( η p 2 = .59, p< .001), 360°Empty ( η p 2 = .43, p = .006). Active intervention participants showed significant improvement from pre-intervention to 10-week follow-up on all measures. Findings illustrate that 360° video VRET is an efficacious way to significantly reduce PSA, social anxiety and FNE.